LATIN SQUARE DESIGN ANALYSIS OF THE EFFECT OF NPK AND UREA FERTILIZER: AN APPLICATION TO THE YIELD OF TOMATO - ADAMU, A,; BELLO, A.,; NASIR, ISA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
Fertilizers are essential to modern farming (Agriculture), their overuse can have harmful effects on human being, plants, crops and soil quality in general (Popoola, et al., 2015). Thus, this paper attempts to develop a model that investigates the effects of NPK and Urea fertilizer on the yield of tomato (Lycopersicum Esculentum), examine if the NPK and Urea fertilizers contribute to the growth and yield of tomato. The paper also detects which of the NPK or Urea components contribute most to the yield of tomato. It thus determines further at what proportion each of the NPK and Urea is to be applied for optimum yield if applied correctly, confirm the optimum yield at kilogram per square (hectare). Latin Square Design ANOVA was adopted in the analysis to determine if the NPK and Urea fertilizers used have effect on the tomato. Post Hoc analysis was carried out using Least Significant Difference (LSD) test to determine which level of the NPK and Urea fertilizers differed. The result of the analysis showed that NPK and Urea fertilizers contribute immensely to the growth and yield of tomato at the different zones of the state as well as different levels of fertilizer application. Furthermore, the overall model for the yield of tomato was also obtained and can be described as good.